Construction Contract Administration for Project Owners - Lancome, Claude G., author (Abingdon, Oxon ; New York, NY : Routledge, 2017)
Project delivery methods -- Techniques for effective preparation of contracts -- Techniques off contract administration -- Key issues in drafting the designer agreement -- Administering the design agreement -- Drafting and administering consultant agreements -- Key issues in drafting the construction contract -- Administering the construction contract -- Change orders and claims -- Closing out the construction contract